Study of the internet latent corpus on active methodologies and digital technologies in Science teaching - Bruno Silva Leite (Universidade Federal do Oeste da Bahia, 2020)
Active methodologies and digital technologies are very present in the teaching and learning processes, both in Brazil and in the world. When dealing with this theme, this work aimed to identify which articles, through the Internet latent corpus, were elaborated in a natural context about active methodologies and digital technologies in science teaching. For this, we surveyed publications in Portuguese involving the theme highlighting its relevance and application. Our data corpus was Google Scholar and the kind qualitative analysis. The results show that although the researches on the integration of these technologies are in an early stage, we can affirm that those carried out so far demonstrate the great benefits they incorporate into the teaching-learning process. Among these contributions, we can highlight the motivation, satisfaction, and autonomy. Besides, we infer some possibilities of active technological learning and personalized learning in science teaching.